Conversion of biowaste to biogas: A review of current status on techno-economic challenges, policies, technologies and mitigation to environmental impacts. (15th October 2021) - Glivin, Godwin; Kalaiselvan, N.; Mariappan, V.; Premalatha, M.; Murugan, P.C.; Sekhar, Joseph
Graphical abstract: Highlights: Anaerobic Digesters contribute to decentralised energy generation. Proper study on biowastes types and availability improves conversion efficiency. Biochemical conversion is economically feasible in rural areas. New generation of biomass and technologies could contribute to clean energy. Multistage digestion and solar thermal energy improve conversion efficiency. The economic benefits in utilizing the digestate as chemical fertilizer. Abstract: Anaerobic Digestion (AD) could be a promising methodology to convert biowastes to sustainable fuel for applications like power generation, heating, drying, cooling and so on. Forceful amendment in technologies, government policies, social behavior and economic aspiration cause vital analysis of those factors for successful generation of energy from biowastes. To accomplish the need, the current review deals with the status of biowastes utilization, biowaste conversion technologies and influencing parameters of the conversion process. This paper conjointly reviews totally different pre-treatment and co-digestion ways that improve the effectiveness of AD. Moreover, the economic merits of these well-studied technologies are summarized and compared in terms of autoclave performance, environmental advantages, and the status of real-world applications.